Perkembangan Pemaknaan Measurand Isovist dalam Penerapannya untuk Kuantifikasi Pengalaman Spasio-Visual pada Desain - Vegantara, Vanidia; Lionar, Mario Lodeweik (Nature : National Academic Journal of Architecture, 2025)
Vision is the most active information processing system and is the primary stimulus for understanding and capturing surrounding experiences, making visual elements significant in design. In this context, isovists provide a general spatio-visual representation of space to quantitatively measure the spatial properties of an environment. This article discusses the development of isovist use in the fields of architecture and urban planning, as well as the interpretation of isovist parameters in relation to the spatial-visual expression of space. The literature analysis method used in this study led to the conclusion that the use of the isovist method is not limited only to buildings alone, but has also expanded to broader scopes such as urban planning and to detailed scopes like interior design. The isovist measurands (things that can be measured) can be indicators in quantifying spatial expression, which include prospect, refuge, mystery, and compactness. The results of this study contribute to the interpretation of measurements in their application for quantifying the spatio-visual characteristics of space, which can be utilized by both researchers and designers.